2018
DOI: 10.3389/fmicb.2018.00018
|View full text |Cite
|
Sign up to set email alerts
|

Stress Tolerance-Related Genetic Traits of Fish Pathogen Flavobacterium psychrophilum in a Mature Biofilm

Abstract: Flavobacterium psychrophilum is the causative agent of bacterial cold-water disease and rainbow trout fry syndrome, and hence this bacterium is placed among the most important salmonid pathogens in the freshwater aquaculture industry. Since bacteria in biofilms differ substantially from free-living counterparts, this study sought to find the main differences in gene expression between sessile and planktonic states of F. psychrophilum LM-02-Fp and NCMB1947T, with focus on stress-related changes in gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…This result should not be extrapolated to in vivo infection cases of salmonids or other bacterial species. For instance, another study that used Flavobacterium psychrophilum and the CHSE-214 cell line demonstrated higher virulence in the biofilm state than in the planktonic state 47 . However, the aforementioned lack of differences in P. salmonis-induced cytotoxicity between www.nature.com/scientificreports/ biofilm-derived and planktonic bacteria has also been found when infecting the CHSE-214 cell line with P. salmonis LF-89 T and CA5 (results from another yet-unpublished study by our team).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result should not be extrapolated to in vivo infection cases of salmonids or other bacterial species. For instance, another study that used Flavobacterium psychrophilum and the CHSE-214 cell line demonstrated higher virulence in the biofilm state than in the planktonic state 47 . However, the aforementioned lack of differences in P. salmonis-induced cytotoxicity between www.nature.com/scientificreports/ biofilm-derived and planktonic bacteria has also been found when infecting the CHSE-214 cell line with P. salmonis LF-89 T and CA5 (results from another yet-unpublished study by our team).…”
Section: Discussionmentioning
confidence: 99%
“…This result should not be extrapolated to in vivo infection cases of salmonids or other bacterial species. For instance, another study that used Flavobacterium psychrophilum and the CHSE-214 cell line demonstrated higher virulence in the biofilm state than in the planktonic state 47 . However, the aforementioned lack of differences in P .…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas cyclic lipopeptides (or CLPs) are surface-active metabolites synthesized non-ribosomally by modular multifunctional enzymes named non-ribosomal peptide synthetases (NRPSs) [ 1 ]. Structurally, CLPs comprise a cyclic oligopeptide lactone ring linked to a fatty acid tail [ 2 ]. These molecules mediate multiple biological functions, including biofilm formation, swarming motility, virulence (in plant pathogenic strains), antibacterial, antifungal, anti-oomycete, insecticidal, anti-carcinogenic and antiviral properties [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, CLPs comprise a cyclic oligopeptide lactone ring linked to a fatty acid tail [ 2 ]. These molecules mediate multiple biological functions, including biofilm formation, swarming motility, virulence (in plant pathogenic strains), antibacterial, antifungal, anti-oomycete, insecticidal, anti-carcinogenic and antiviral properties [ 2 , 3 , 4 , 5 , 6 , 7 ]. These bioactive molecules are produced by specific species within the P. syringae complex, P. fluorescens, P. putida and P. asplenii groups [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation